Clinical Profile and Outcome of Neonates Admitted to Neonatal Intensive Care Unit of NGMC - KM, Roma; Pyakurel, Manita; Gupta, Veena; Kanodia, Piush (Journal of Nepalgunj Medical College, 2017)
Background: Neonatal period is a period from birth to under 28 days of life. The common causes of mortality and morbidity in our region are preventable, among which neonatal sepsis is the commonest one. Most of the deaths occur within 7 days of life. Objectives: To study the clinical profile, pattern of diseases, causes of morbidity and mortality amongst newborns. Materials and methods: A hospital based descriptive study was done among total 967 newborns including both inborn and out born admitted in NICU, NGMC from January 2016 to December 2016. Age, sex, gestational age, diagnosis at admission, outcome of admitted th newborns were the main variables under study. Data was entered in Excel and analyzed using SPSS 20th version. Data were presented through pie, bar graph and table with frequency and percentage. Results: Male were predominant in the study (65%). One third of the admitted newborns were preterms. Half of the admitted newborns were admitted on their first day of life. Neonatal sepsis was the most common cause of admission. Deaths occured in 7.4%of total babies. Seventy-six percent got improved after treatment. Only 2.8% were referred to higher center. Conclusions: Most of the neonates got admitted in first day of life with commonest cause being neonatal sepsis. Recovery rate was satisfactory. To reduce the mortality and morbidity of neonates, we need to increase awareness level in general population and proper aseptic practices in medical practitioners.